Quaestio Vexata: Collecting Arundel “Chromos” in America and Australasia - Ward, Lucina (Australasian Journal of Victorian Studies, 2021)
Frederick McCubbin (1855–1917), watching students copy chromolithographs and casts in Melbourne’s National Gallery School of Art, concluded it was “no end of a place to study”. The Arundel Society’s prints and other works of art acquired by the Public Library, Museum and Gallery reveal the alignment of education with the elevation of taste. The School’s use of the collection was not unusual at the time, and the tradition of copying in art education continued into the twentieth century. More worthy of remark, perhaps, are the students’ models: the Society published trecentro and quattrocento frescoes from northern and central Italy, as well as altarpieces by van Eyck, Memling and others. The prints, fictile ivories, photographs and texts produced by the Arundel Society (1848–1897) were disseminated from Britain around the world. The high-quality colour lithographs were available framed and glazed. They were used for reference, as objects of veneration or for interior decoration. The Society promoted its subscribers: members of the aristocracy, politicians, churchmen, scholars and artists; these included, for a time, the Pre-Raphaelites William Holman Hunt and William Morris. Writers such as William Rossetti, in the New York journal The Crayon in the 1850s, and James Smith in The Argus in Melbourne in the 1860s, devoted substantial space to the Society’s didactic aims and preservation activities. This richly-illustrated paper explores the vexed question of Arundel Society chromolithographs in museum collections, and their impact on the nascent discipline of art history. It examines intellectual networks in Australia and other British colonies, as well as American and European patterns of circulation, to consider knowledge of ‘the Primitives’ and expectations about art.